2017
DOI: 10.1038/bcj.2017.12
|View full text |Cite
|
Sign up to set email alerts
|

Bi-allelic inactivation is more prevalent at relapse in multiple myeloma, identifying RB1 as an independent prognostic marker

Abstract: The purpose of this study is to identify prognostic markers and treatment targets using a clinically certified sequencing panel in multiple myeloma. We performed targeted sequencing of 578 individuals with plasma cell neoplasms using the FoundationOne Heme panel and identified clinically relevant abnormalities and novel prognostic markers. Mutational burden was associated with maf and proliferation gene expression groups, and a high-mutational burden was associated with a poor prognosis. We identified homozygo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 32 publications
3
49
0
2
Order By: Relevance
“…For tumor suppressors, we found frequent instances of biallelic inactivation through mutations and deletions that were particularly notable for TP53 in which 6 of 7 patients showed both a mutated and a deleted allele (Figure 2A-B). 23,54 Combining CNAs and mutations, our selected cohort of double-resistant patients showed inactivation of the TP53 pathway through mutations and/or deletions in 45% of the patients ( Figure 2C), more than what was previously reported in NDMM. In paired samples from the CoMMpass cohort, we also observed the same phenomenon (supplemental Figure 4A).…”
Section: Genomic Makeup Of Treatment-resistant Samplessupporting
confidence: 46%
“…For tumor suppressors, we found frequent instances of biallelic inactivation through mutations and deletions that were particularly notable for TP53 in which 6 of 7 patients showed both a mutated and a deleted allele (Figure 2A-B). 23,54 Combining CNAs and mutations, our selected cohort of double-resistant patients showed inactivation of the TP53 pathway through mutations and/or deletions in 45% of the patients ( Figure 2C), more than what was previously reported in NDMM. In paired samples from the CoMMpass cohort, we also observed the same phenomenon (supplemental Figure 4A).…”
Section: Genomic Makeup Of Treatment-resistant Samplessupporting
confidence: 46%
“…8 ). SVs also led to loss of tumor suppressor genes such as BIRC2/3 , CDKN2A/B, CDKN2C , TRAF3 30 and FAM46C , either within focal deletions or more complex events. These data confirm that SVs, accessing both simple and complex mechanisms of genome rearrangement, is a major force shaping the myeloma genome.…”
mentioning
confidence: 99%
“…37 Biallelic inactivation of recurrently altered tumor suppressor genes has recently been suggested as a key driver mechanism of disease progression in MM. 38,39 With the D006 digitalMLPA probemix, homozygous losses of CDKN2C/FAF1, BIRC3, TRAF3, and TP53 were detected, which were reported to be affected by biallelic deletions in MM and being enriched at the time of relapse. Notably, homozygous deletions in CYLD, which was found in a patient in a previous study 40 but was not analyzable by the targeted FoundationOne Heme panel in a recent study, 38 could also be identified.…”
Section: Discussionmentioning
confidence: 99%